Frequency of Pericardial Effusion after Acute Anterior Wall Myocardial Infarction Presenting at Tertiary Care Hospital, Peshawar - Sajjad, Wasim; Rehman, Sami ur; Latif, Abdul; Rahim, Abdur; Ullah, Rahid; Jan, Daud Ahmad; Bilal, Hafiz Adil (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To determine the frequency of pericardial effusion after acute anterior wall myocardial infarction. Design of the Study: Cross sectional study. Study Settings: The study was conducted at Cardiology Department, Lady Reading Hospital, Peshawar from 13/5/2019 to 13/11/2019. Material and Methods: Total of 122 patients were included. Baseline investigation including ECG (cardiofax) and transthoracic echocardiography (Siemens’ Accuson CV-70), was done within 72 hours of acute anterior wall myocardial infarction. All the information like for age, gender, hypertension, diabetes, previous history of CAD, and smoking were recorded. Results of the Study: In this study mean age was 63 years with standard deviation ±8.99. Sixty two patients were male while 38% patients were female. More over 24% patients had pericardial effusion and 76% patients didn’t had pericardial effusion. More over 24% patients had pericardial effusion and 76% patients didn’t had pericardial effusion. Conclusion: Conclusion of our study states that the frequency of pericardial effusion was 24% after acute anterior wall myocardial infarction.